مستوى أداء الوظائف الأساسية للإدارة في الاتحاد العربي السوري لكرة القدم وعلاقتها بمداخل صنع القرار الاستراتيجي دراسة ميدانية على عمل اللجنة الفنية لكرة القدم في دمشق - معوض, وائل; بشارة, لبنى; السباعي, أنس (Latakia University Journal -Medical Sciences Series, 2019)
The strength of the organizations and their ability to continue, compete and achieve the objectives is mainly through their work on the development of strategic decisions in accordance with the right and appropriate approach to their internal and external resources in a dynamic environment. The administrative performance represents one of its actual executive forms. Thus, the level of performance of the basic functions of the administration in the work of the technical committee of football in Damascus was examined and the nature of the relationship with strategic decision-making approaches was examined in order to identify the deficiencies and suggest their development. A descriptive analytical approach was used using a questionnaire applied to a sample of (36) members of the technical committee of football in Damascus (1-7 / 2019).The results showed that the basic functions of the Department and strategic decision-making approaches of all kinds (incremental, comprehensive, Cangarbage, and natural approach) are practiced to a moderate extent in the work of the Technical Committee of Football, but the adoption of a comprehensive or incremental approach in strategic decision-making will affect the results of the performance of the basic functions of management in the work of the technical committee of football, Statistically significant relationship between these variables. The most important recommendations: the need for managers to recognize the importance of the relationship between the strategic decision-making approach and the performance of the basic functions of management and it is important that the vocabulary of this perception reflected on the reality of work. تتجلى قوة المنظمات وقدرتها على الاستمرار والمنافسة وتحقيق الأهداف بشكل أساسي من خلال عملها على تطوير قرارات استراتيجية وفق مدخل صحيح وملائم لمواردها الداخلية والخارجية في بيئة ديناميكية؛ ويمثل الأداء الإداري أحد صورها التنفيذية الفعلية؛ وبذلك تم دراسة مستوى أداء الوظائف الأساسية للإدارة في عمل اللجنة الفنية لكرة القدم في دمشق وتحديد طبيعة العلاقة مع مداخل صناعة القرارات الاستراتيجية؛ وذلك بهدف معرفة مواقع القصور واقتراح تطويرها، وتم استخدام المدخل الوصفي التحليلي باستخدام استبانة طبقت على عينة مكونة من (36) فرداً من اللجنة الفنية لكرة القدم في دمشق في الفترة (1 – 7 /2019) وبينت النتائج أن الوظائف الأساسية للإدارة ومداخل صنع القرار الاستراتيجي بأنواعها (التدرجي والشمولي والحشد العشوائي والطبيعي) تتم ممارستها بدرجة متوسطة في عمل اللجنة الفنية لكرة القدم، لكن اعتماد المدخل الشمولي أو التدريجي في صنع القرارات الاستراتيجية سيؤثر على نتائج أداء الوظائف الأساسية للإدارة في عمل اللجنة الفنية لكرة القدم، نظراً لوجود علاقة ذات دلالة إحصائية بين هذه المتغيرات، ومن أبرز التوصيات: ضرورة أن يدرك المديرون أهمية العلاقة بين مدخل صناعة القرار الاستراتيجي وأداء الوظائف الأساسية للإدارة، وأنه من المهم أن تنعكس مفردات هذا الإدراك على واقع العمل.